Bootstrapping as a Survival Strategy Amid Psychological Pressure and Trust Crisis among Digital Startup Founders in Malang City - Iswari, Hanif Rani; Mas, Nasharuddin; Zahroh, Viony Alfiyatu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
The rise of fraud cases among Indonesian startups has triggered a trust crisis within the funding ecosystem, affecting both investors and entrepreneurs. In this context, some founders opt for bootstrapping not merely due to resource constraints, but as a deliberate response to external pressures and a desire to maintain integrity and business direction. This study employs a descriptive qualitative approach through in-depth interviews with three digital startup founders in Malang City who are currently practicing or have previously practiced bootstrapping strategies. The findings reveal that the decision to reject external funding is influenced by psychological pressure, the need to preserve autonomy, and behavioral biases such as overconfidence and illusion of control. Furthermore, concerns about excessive intervention and reputational risks due to associations with fraudulent practices also reinforce the choice to bootstrap. These findings indicate that financial decisions within startups cannot be separated from the psychological and social contexts surrounding them. Therefore, a more empathetic funding approach that aligns with the personal values of founders is necessary to restore trust and support the holistic sustainability of startups.